2022
DOI: 10.1002/tax.12798
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights on the conflicting generic boundaries in the Carduncellus‐Carthamus complex (Compositae)

Abstract: The Carthamus-Carduncellus complex is formed by approximately 50 taxa that are widely distributed throughout the Mediterranean basin and western Asia. The generic delineation of this complex has always been controversial. Currently, there are three widely diverging taxonomical proposals, suggesting that the complex is formed by (1) a single genus, Carthamus; (2) two genera, Carduncellus and Carthamus; and (3) four genera, Carduncellus, Carthamus, Femeniasia, and Phonus. The generic classification has varied de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
0
0
0
Order By: Relevance
“…The plastid phylogeny showed that C. rhaponticoides was more closely related to F. balearica, which was not consistent with the nuclear phylogenetic trees. The nuclear phylogenetic trees showed C. rhaponticoides clustered with C. pinnatus and F. balearica clustered with P. arborescens, which was consistent with previous studies [24,25,31,32]. Within the Carthamus, our results also show that C. persicus clustered with C. tinctorius × C. persicus and C. tinctorius, with the three having a closer relationship, all belonging to sect.…”
Section: Phylogeny Of Carthamus Speciessupporting
confidence: 91%
See 1 more Smart Citation
“…The plastid phylogeny showed that C. rhaponticoides was more closely related to F. balearica, which was not consistent with the nuclear phylogenetic trees. The nuclear phylogenetic trees showed C. rhaponticoides clustered with C. pinnatus and F. balearica clustered with P. arborescens, which was consistent with previous studies [24,25,31,32]. Within the Carthamus, our results also show that C. persicus clustered with C. tinctorius × C. persicus and C. tinctorius, with the three having a closer relationship, all belonging to sect.…”
Section: Phylogeny Of Carthamus Speciessupporting
confidence: 91%
“…Atractylis. To objectively evaluate the Carduncellus-Carthamus complex, Vilatersana et al performed a phylogenetic analysis using nrITS and plastid markers, highlighting the subdivision of the complex into four genera: Carduncellus, Carthamus, Phonus, and Femeniasia [25]. Despite the widespread use of cp genomes in species identification and evolutionary studies, limited studies have been carried out on the cp genome of Carthamus species.…”
Section: Introductionmentioning
confidence: 99%